Research on the impact of career advancement on the mental health of young workers - Hanwei Li; Xiaoheng Wu (PLoS ONE, 2025)
Mental health is an important component of overall health. Currently, the mental health issues among Chinese workers are becoming increasingly severe, especially under the backdrop of increased uncertainty in career advancement, where depression and anxiety issues among young workers are prominent. Based on the panel data from the China Family Panel Studies (CFPS) in 2018 and 2020, this paper constructs an OLS regression model to empirically analyze the impact of career advancement constraints on workers’ mental health and its mechanism of action. The study finds that limited career advancement significantly increases workers’ depression index. Pathways such as extended working hours, deteriorated health conditions, and distorted labor value concepts play a partial mediating role, thereby reducing mental health levels. Heterogeneity analysis shows that compared to female, low-income, and low-educated individuals, male, those with medium to high income, and higher education levels are more likely to experience a decline in mental health due to career advancement constraints. This study provides empirical evidence for understanding the impact of career advancement uncertainty on mental health and offers important insights for improving occupational mental health policies and enhancing worker welfare.